2020
DOI: 10.21203/rs.3.rs-30288/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Relationships between motor scores and cognitive functioning in FMR1 female premutation X carriers indicate early involvement of cerebello-cerebral pathways.

Abstract: Background Smaller expansions of CGG trinucleotide repeats in the FMR1 X-linked gene termed ‘premutation’ lead to a neurodegenerative disorder: Fragile X Associated Tremor/Ataxia Syndrome (FXTAS) in nearly half of aged carrier males, and 8-16% females. Core features include intention tremor, ataxia, and cognitive decline, and white matter lesions especially in cerebellar and periventricular locations. A ‘toxic’ role of elevated and expanded FMR1 mRNA has been linked to the pathogenesis of this disorder. The em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 58 publications
(69 reference statements)
0
1
0
Order By: Relevance
“…Increased age was associated with decreased stride length and increased cadence CoV in the FMR1 premutation carriers, while age was not associated with any gait measurements in the healthy controls. This finding demonstrates that premutation carriers may show an earlier or more rapid decline in gait control relative to healthy aging [ 3 , 4 , 76 , 77 ], though it should be noted that our control group was younger than our FMR1 premutation carriers ( Table 1 ). We also found that lower IQ was associated with an increased cadence CoV and COM standard deviation in the healthy controls, but not in the FMR1 premutation carriers, suggesting that sensorimotor and broader cognitive issues may be independently affected during aging in premutation carriers.…”
Section: Discussionmentioning
confidence: 78%
“…Increased age was associated with decreased stride length and increased cadence CoV in the FMR1 premutation carriers, while age was not associated with any gait measurements in the healthy controls. This finding demonstrates that premutation carriers may show an earlier or more rapid decline in gait control relative to healthy aging [ 3 , 4 , 76 , 77 ], though it should be noted that our control group was younger than our FMR1 premutation carriers ( Table 1 ). We also found that lower IQ was associated with an increased cadence CoV and COM standard deviation in the healthy controls, but not in the FMR1 premutation carriers, suggesting that sensorimotor and broader cognitive issues may be independently affected during aging in premutation carriers.…”
Section: Discussionmentioning
confidence: 78%